Residues of veterinary drugs in fish and fish products: An analysis of RASFF data over the last 20 years. (May 2022) - Guardone, L.; Tinacci, L.; Armani, A.; Trevisani, M.
Abstract: An analysis of the notifications in the European Union (EU) Rapid Alert System for Food and Feed (RASFF) portal due to residues of veterinary drugs in fish and fish products over the period 2001–2021 was conducted examining the following data: number and type of notifications; year of notification; notification basis; notifying country; country of origin; action taken; distribution status; risk decision; fish product type; residue found. A total of 292 notifications were found (mean number/year 9.8 ± 13.8 SD), mostly information notifications (60.9%). The most common notification basis was "border control - consignment detained" (38.4%), followed by "official control on the market" (37.9%) and "border control - consignment released" (13.7%). Over half (54.1%) of the notifications were issued by the United Kingdom, Germany and Spain, dominant countries in the fish processing market. Thirty-one countries of origin were recorded, but 48.6% of the notifications were referred to products from Vietnam, followed by China (15.7%), that are among the leading fish producing countries. The most common actions taken were re-dispatch (23.3%), followed by recall from consumer (10.3%), withdrawal from recipients (9.9%), destruction (9.6%), and import not authorised (9.2%). Overall, 28.8% of the notifications involved fish products belonging to the Pangasiidae family ( Pangasius spp. and Pangasianodon spp.), followed by tilapia (12.7%), trout (11.0%), eel (8.6%), catfish (7.9%) and salmon (3.4%). Triphenylmethane dyes and their metabolites were the most frequent category of residues found, accounting for 51.4% of the total notifications, followed by a wide range of antibiotics classes, of which nitrofurans and metabolites (19.5%) were the most common, while amphenicols (6.8%), quinolones and fluoroquinolones (6.5%), sulphonamides and potentiators (5.1%), tetracyclines and metabolites (3.4%) and other classes were less represented. Avermectins and unspecified residues were also found in a few cases (2.7%). The annual frequency of these issues varied and was probably influenced by dedicated monitoring plans, as well as by specific sanitary problems occurring in farms. Nevertheless, by providing historical trends and current issues, our analysis identified hazards to be closely monitored, through coordinated official controls especially in the most involved countries. Highlights: 20 years of RASFF notifications for veterinary drugs residues in fish products were analysed. Triphenyl-methane dyes were the most frequent residue found (51.4% notifications). Several antibiotics classes were found, mainly nitrofurans (19.5% of the notifications). Historical and current issues to be specifically monitored were pointed out.